COMPETENCES OF THE HIGHER LEVEL: APPROACHING NEW MODALITIES OF TRANSVERSAL IMPLEMENTATION (Journal of Industrial and Mechanical Engineering, 2020)
This research arises from seeing that many institutions try to develop their curricula by competencies and with it, train students by competencies, but not many manage to do so.According to Zabalza (2015), universities that want to transform their curricula to one based on competencies need to overcome many obstacles in order to be successful.Among the challenges that universities must overcome are: 1) Adapt to job demands; b) To be situated in a highly competitive context where quality and the capacity for change are required; c) Improve management; d) Incorporate new technologies in both management and teaching; e) To become an engine of local development, both culturally and socially and economically; f) Relocate to a globalized scenario, which implies promoting interdisciplinary, command of foreign languages, mobility of teachers and students, and shared accreditation systems.
Keywords: competencies; education; university